Let them eat Prozac - Healy, David, 1954- (Toronto : James Lorimer & Company, 2003)
"A compelling story about mystery, deception, death, disappointment, vindication, and uncertainty." -'The American Psychological Association' "Healy confirms his status as one longtime thorn in the side of big drug companies, recounting how he was initially enthusiastic about SSRIs but eventually grew concerned about their side effects." -'Psychology Today' "Physicians should be aware of Let Them Eat Prozac ." -'JAMA'" Let Them Eat Prozac is a double-pronged exploration, first of the SSRI drugs used to treat depression, and second of the drug industry." -'Publishers Weekly'"Ultimately, the book is about science, society and the power and misuse of commercial promotion. . . . His investigation is impressive." -'Nature'"This very important book will demonstrate beyond your worst dreams that the commercial needs of Big Pharma are the natural-born enemy of independent scientific research." -John Le Carr"Healy presents technical matters clearly. This book could not be more timely." -'Foreword'" Let Them Eat Prozac is an interesting history. It asks some stimulating and challenging questions, which are still in need of better and more constructive answers." -'Journal of the American Academy of Child Adolescent Psychiatry' In a flood of academic publications and talks, David Healy has issued harsh criticisms of both the pharmaceutical industry in general and the nearly $20-billion-dollar-a-year antidepressant industry in particular." -'Boston Globe'"Healy does raise some timely issues." -'Psychiatric Services'"Dr. Healy's tenacity in fighting for what he believes in is admirable." -'E-Streams'"[Healy is] the leading authority on the history of psychopharmacology." -'Times Literary Supplement'An alarming book. . . . The most disturbing part of the story Healy tells is not merely about the risks of SSRIs but about the efforts of the pharmaceutical industry to make sure those risks were not uncovered. -'Dissent'"In his timely new book, Healy draws on his extensive ex
Take one -- Events in Kentucky -- Down the barrel of a lawyer -- Market force -- A Pacific fault line -- Kafka's Castle -- Experiment at the end of the millennium -- The plots thicken -- The tort wars -- Let them eat Prozac -- Epilogue: anecdotal deaths.
Includes bibliographical references (p. 289-340) and index.
Keywords: Depression, Mental -- Chemotherapy; Depressive Disorder -- Drug therapy; Drug Industry -- Ethics; Fluoxetine -- Adverse effects; Fluoxetine -- Therapeutic use; Fluoxetine; Klinische psychologie -- Specifieke problemen; Psychotropic drugs industry; Serotonin uptake inhibitors